In vitro pharmacological and synergistic effects of herbal concoctions sold in Ga Maja, Limpopo Province - Matotoka, Mashilo Mash (University of Limpopo, 2019)
Informal street traders and traditional health practitioners at Ga Maja (Limpopo Province) primarily offer consumers semi-processed herbal concoctions that are indicated to have blood-cleansing, immune-boosting, detoxifying, antidiarrheal, antiHIV/AIDS and pain-relieving therapeutic properties. The focus of this study was to validate the pharmacological effects and safety of these herbal concoctions as indicated by the traders. Five herbal concoctions and their medicinal plant recipies used for their preparation were purchased from five independent traders. A laboratory concoction was prepared according to the traders’ instructions. Possible microbial contaminants were identified using Matrix-assisted laser desorption/ionisation time-offlight mass spectrometry and VITEK 2. Nutritional content of the concoctions was determined by a plasma atomic emission spectrophotometer. Qualitative phytochemical analysis was determined using standard chemical tests and thin layer chromatography. Total polyphenol content was quantified calorimetrically. Antioxidant activity was quantified using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing power assays. Antimicrobial activities were determined using a broth micro-dilution assay and bioautography. Anti-HIV-1 reverse transcriptase activity was used to determine the antiviral potential of the concoctions. Anti-inflammatory activity was determined using the cyclooxygenase inhibition assays and possible cytotoxic effects of the concoctions were evaluated using MTT cell viability assay. Growth on potato dextrose and nutrient agar plates indicated heavy microbial contamination. Sodium, potassium and zinc were most abundant in the concoctions. The concoctions had similar phytochemical profiles, and together with plant decoctions consisted primarily of polyphenolic constituents. Generally, some plant decoctions had higher antioxidant (EC50: 15.71 – 40.87 µg/mL) and antibacterial (MIC: 0.04 – 0.63 mg/mL) activities. The antimicrobial activities of the concoctions were as a result of synergistic effects of the compounds because no single compound was observed to have antimicrobial activities on the bioautograms. Combination studies showed that the combination of crude decoctions from different plant species resulted in reduced antioxidant, antibacterial and antifungal activities. The laboratory concoction had higher anti-HIV reverse transcriptase activity (EC50: 2.90 µg/mL) than the positive controls used (EC50: 36.65 – 40.90 µg/mL). The concoctions also demonstrated considerable antiinflammatory activity. The lack of standardisation of phytomedicines reduces their xxi pharmacological potential and consistency. However, this study validated the ethnopharmacological use of the different plant species and herbal concoctions towards the treatment of human immune-deficiency virus, pain caused by inflammation, infectious diarrhoea and for immune-boosting. This study also highlighted the complexities associated with combinations of aqueous extracts and the importance of appropriate knowledge on which plant species are to be mixed to enhance their therapeutic properties. Although the concoctions did not exhibit cyctotoxic effects, toxicities may arise from endotoxins produced by the microbial contaminants. Hygienic processing and packaging are essential to ensure that consumers receive quality products that are safe to consume.
Thesis (M. Sc. (Microbiology)) --University of Limpopo, 2019
Keywords: Vitro pharmacological and synergistic effects; Herbal concoction; Ga Maja; Informal street traders; Traditional health practitioners; Traditional medicine; Ethnopharmacology